Social Inequalities in Dog Bites and Strikes in Scotland: Evidence from Administrative Health Records and Implications for Prevention Policy - Jade Hooper; Hannah M. Buchanan-Smith; Tony Robertson; Paul Lambert (Animals, 2025)
This paper reports findings on the social patterning of dog bite injuries in Scotland and discusses their implications for prevention policies. Previous studies have shown evidence of social inequalities in dog bites in other countries, but this analysis provides new evidence about Scotland. Three sources of health record data are used (NHS 24 (telephone) records, accident and emergency department records, and hospital admissions records). The records span the period of 2007–2019 and combine information on 59,111 health records involving injuries caused by dogs (from 48,599 different individuals). The results are presented, summarising the volume of dog bite injuries across time periods by the age of respondents, the location of the incident, and the Scottish Index of Multiple Deprivation categorisation for their locality. The results suggest consistent patterns of social inequality in injuries caused by dogs. We argue that the most important finding concerns the higher risk for people from more deprived areas, and we discuss mechanisms that might lie behind the patterns and how policies might respond to them. Existing policies focus on the breed of dog and punitive strategies, but we argue that different approaches are more likely to be effective in addressing a socially stratified public health issue.